Respuesta :

Answer:

D


Step-by-step explanation:

We find the area of a rectangle by multiplying the lengths of both the sides (length and width).

  • One side given is [tex]x+3[/tex]
  • Another side given is [tex]2-x[/tex]

Multiplying these 2 will give us the expression for the area of the rectangle (we use distributive property given by  [tex]a(b+c)=ab+ac[/tex] in this problem to multiply)

Area = [tex](x+3)(2-x)\\=2x-x^2+6-3x[/tex]

Now combining like terms and rearranging, we have:

[tex]2x-x^2+6-3x\\=-x-x^2+6\\=-x^2-x+6[/tex]


Answer choice D is right.


Answer:

D

Step-by-step explanation:

distributive property:

2x - x^2 + 6 - 3x

simplify:

-x^2 - x + 6